Material Weakening of Slip Zone Soils Induced by Water Level Fluctuation in the Ancient Landslides of Three Gorges Reservoir - Yu-Yong Jiao; Liang Song; Hui-Ming Tang; Yun-An Li (Advances in Materials Science and Engineering)
This experimental study investigated the effect of repeated wetting and drying on the reduction of slip zone soils taken from the Huangtupo landslide in the Three Gorges Reservoir, China. The variation process of the physical property and substance composition of the slip zone soils under the wetting-drying cycles was studied through liquid and plastic limit test and X-ray diffraction test. The results indicate that (1) the shearing strength of the slip zone soil dramatically decreased after one wetting-drying cycle and then gradually decreased until reaching a relatively stable state at the fourth cycle; (2) the plasticity index of the slip zone soil varied with increasing number of cycles and a variation process opposite to that of the strength value was observed; and (3) the clay mineral content in the slip zone soil increased and the calcite and quartz contents relatively decreased with increasing number of cycles. The variations in the plasticity index of the slip zone soil, as well as the increase in its clay mineral content, play important roles in the strength reduction. The results of this study provide a foundation for revealing the deformation and damage mechanism of landslides in reservoir banks.